The Plum Thicket - Giles, Janice Holt (Book collections on Project MUSE., 1996)
Janice Holt Giles had a life before her marriage and writing career in Kentucky. Born in Altus, Arkansas, Giles spent many childhood summers visiting her grandparents there. After the success of her historical novel The Kentuckians in 1953, she planned to write a second frontier romance. But a visit to Altus caused her imagination to drift from Kentucky in 1780 to western Arkansas in 1913. At age forty-eight -- the same age as Giles at the writing of the novel -- the heroine Katie Rogers recalls her first visit alone to her grandparent's home in Stanwick, Arkansas. Eight-year-old Katie spends ...